Effects of lowering dietary NDF levels prior to marketing on finishing pig growth performance, carcass characteristics, carcass fat quality, and intestinal weights - M D Asmus; Michael D Tokach; Steven S Dritz; Terry A Houser; Joel M DeRouchey; Jim L Nelssen; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 2011)
A total of 264 pigs (PIC 327 × 1050, initially 90.1 lb) were used in a 90-d study to determine the effects of withdrawal of high dietary NDF (provided by wheat middlings [midds] and dried distillers grains with solubles [DDGS]) on growth performance, carcass characteristics, carcass fat quality, and intestinal weights of growing-finishing pigs. Pens of pigs were randomly allotted by initial weight and gender to 1 of 6 dietary treatments with 6 replications per treatment. There were 24 pens with 7 pigs per pen (3 barrows and 4 gilts) and 12 pens with 8 pigs per pen (4 barrows and 4 gilts). A positive control diet containing no DDGS or midds and a negative control diet containing 30% DDGS and 19% midds was fed the entire study duration (no withdrawal). The other 4 treatments were arranged in a 2 × 2 factorial with the main effects of with- drawal time (23 or 47 d) and NDF level fed during the withdrawal (low or medium). Pigs on these treatments were fed the negative control diet containing 30% DDGS and 19% wheat midds (19% NDF) prior to their withdrawal treatment. The medium fiber withdrawal diet contained 15% DDGS and 9.5% midds (14.2% NDF). The low-fiber withdrawal diet was the positive control diet without DDGS or midds (9.3% NDF). Increasing the duration of the withdrawal lowered overall ADFI (linear, P<0.03) and improved F/G (linear, P<0.004); however, overall ADG was not affected. Withdrawing the high-fiber diet for the last 23 d did not influence (P>0.61) growth performance. Withdrawing the high-fiber diet improved carcass yield (P<0.004) with a greater response (P<0.001) when the low-NDF diet was fed during the withdrawal instead of the medium NDF diet; however, increasing the withdrawal time from 23 to 47 d did not further improve yield (P = 0.11).; Swine Day, Manhattan, KS, November 17, 2011
Keywords: Swine Day; 2011; Kansas Agricultural Experiment Station contribution; no. 12-064-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1056; Swine; DDGS; Fiber; Finishing pig; NDF; Wheat middlings; withdrawl